2020
DOI: 10.48550/arxiv.2009.14471
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

PettingZoo: Gym for Multi-Agent Reinforcement Learning

Abstract: OpenAI's Gym library contains a large, diverse set of environments that are useful benchmarks in reinforcement learning, under a single elegant Python API (with tools to develop new compliant environments) . The introduction of this library has proven a watershed moment for the reinforcement learning community, because it created an accessible set of benchmark environments that everyone could use (including wrapper important existing libraries), and because a standardized API let RL learning methods and enviro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
41
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(44 citation statements)
references
References 24 publications
0
41
0
Order By: Relevance
“…In this section, we evaluate the proposed CAC using two environments: 1) the cooperative navigation task in [8], which is built on the OpenAI Gym platform [62], and 2) the pursuit-evasion game [31], which is built on the PettingZoo platform [46].…”
Section: Numerical Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In this section, we evaluate the proposed CAC using two environments: 1) the cooperative navigation task in [8], which is built on the OpenAI Gym platform [62], and 2) the pursuit-evasion game [31], which is built on the PettingZoo platform [46].…”
Section: Numerical Resultsmentioning
confidence: 99%
“…In this case, the shared component θ s i can serve as such a common feature extractor. From many empirical results on RL [45,31,46], a robust feature extractor is highly beneficial for agents to improve their stability and practical performance. Moreover, in a closely related area of federated learning, it has also been observed that partially personalized models improve the generalization power among different agents, leading to better feature representations [47,48,49].…”
Section: The Proposed Formulationmentioning
confidence: 99%
“…While multi-agent reinforcement learning (MARL) is a well-established branch of Deep RL, most learning algorithms and environments proposed have targeted a relatively small number of agents 17,41 . It is common to see environments with less dozens of agents 1,30,52,67 , with 2-agent and 4-agent environments being particular popular for the study of competitive, self-play settings 2,23,36 . Collective intelligence observed in nature, however, rely on a much larger number of individuals than typically studied in MARL, involving population sizes from thousands to million.…”
Section: Multi-agent Learningmentioning
confidence: 99%
“…1) General MARL Framework: The development of MARL is relatively new compared to its single-agent counterpart, and there is currently no commonly and widely used MARL framework. PettingZoo [10], a Python library, has a goal of developing a universal application programming interface (API) for formulating MARL problems, as OpenAI Gym [11] did for single-agent RL problems. However, because the key advantages of PettingZoo-namely, an efficient formulation suitable for the turn-based games and an ability to handle agent creation and death within episodes-are less relevant to power system control problems, PowerGridworld does not adopt the PettingZoo APIs at this stage for simplicity.…”
Section: B Related Softwarementioning
confidence: 99%